Parameter optimization and microstructure evaluation of welding of structural steel 1020 and AA6062. (1st January 2023) - Kumar, C Labesh; Jayakumar, V; Bharathiraja, G; Palani, Kumaran
Abstract: AA6062 and ST1020 materials are used to perform friction stir spot welding (FSSW). In this experiment, the mechanical and microstructural characteristics of the welded joint were determined using a square-head tip tool. To enhance the life of the welded joint, three essential process parameters, namely tool speed, dwell time, and plunge depth were employed with four levels. The L16 orthogonal array was adapted for experimental work to develop a process parameter table. A tensile test was performed for a larger better value to predict the strength of the welded joint, and the value is 5.65 kN. The outcome shows that dwell time is a more prominent parameter than tool speed and plunge depth. The optimal combination of welding parameters is a dwell time of 24 s, a tool rotational speed of 1200 rpm, and a plunge depth of 0.8 mm; dwell time contributes 39.66%, followed by a plunge depth 35.7%, and at last, tool speed 6.171%. Furthermore, to determine the optimum level of parameters. The microstructure of this joint was observed with respect to heat dissipation and changes in grain size. Microstructure studies were carried out to see the area under stir zone for workpieces with high and low tensile strength. This work was validated using the response surface method (RSM). The RSM results are very close to the experimental results.